Differences in the Consumer Literacy of the Nutrition Label across Demographic Factors - Ramdan, Mohamad Rohieszan; Zainol, Zuraidah; @ Zainal Abidin, Juliana Osman; Yahaya, Rusliza (International Business Education Journal, 2016)
The worsening obesity problem in Malaysia has urged various efforts from various parties to address them. The effective use of the nutrition labels is widely accepted and used as one of the efficient measures to address obesity. However, previous studies on the literacy of the nutrition label, especially among Malaysian consumers are still limited. Therefore, this study was conducted to assess the differences in consumers’ literacy of the nutrition label by demographic factors, such as gender, age, education level, income level and ethnicity. This study adopted survey technique and employed a quantitative approach. The sample consisted of 200 respondents, which were selected using random cluster sampling. Data collected were analyzed using Independent Sample T-Test and Analysis of Variance (ANOVA). The results showed that the literacy of the nutrition label varies significantly by gender and ethnicity, but the difference was not significant by age, education level and income level. Specifically, the literacy of the nutrition label is higher among female and Malay. Although these findings provide useful information for designing education and motivation programs towards healthy eating habits among consumers and consequently reduce the obesity problem, this study is limited to a few factors that need for replication and improvements in other studies in the future.